Community Based Tourism sebagai Salah Satu Konsep Pengembangan Pariwisata - Sutama, I Kompyang Gede; Dewi, Nyoman Diah Utari; Rahayu, Luh Riniti (Jurnal Studi Perhotelan dan Pariwisata, 2023)
Purpose: This article aims to investigate the concept and implementation of Community Based Tourism (CBT) as a tourism development strategy that involves the active participation of local communities. Research Methodology: This research uses a descriptive analytical approach by collecting data from literature studies and case studies related to the implementation of CBT in various tourism destinations. Results: The research results show that CBT is able to improve the economic and social welfare of local communities, increase cultural understanding, and maintain the natural environment. Implementing CBT also strengthens local identity and improves the quality of tourist experiences. Limitations: This study is limited to an analysis of available literature and selected case studies, so generalization of findings needs to be done with caution depending on the specific context of each location. Contribution: This article contributes to expanding understanding of the potential of CBT as a sustainable tourism development model that has a positive impact on local communities and the environment, and offers guidance for tourism practitioners and decision makers to implement CBT effectively.